Academic Engagement in Higher Education Research: A PRISMA-Based Systematic Review of Scopus-Indexed Studies (2021–2024) - Nabila Qurrotu Aini; Vina Dartina; Irfan Fahriza; Aisha Nadya; Nadia Khoerun Nissa; Tyas Septiani Savitri (Ma'soem University, 2026)
Academic engagement—students' behavioural, emotional, and cognitive investment in learning—is one of the most robust predictors of achievement, persistence, and well-being in higher education. However, the field is expanding so rapidly that periodic syntheses are needed to map how, where, and with whom engagement is being studied. This systematic review, conducted in accordance with the PRISMA 2020 statement, maps recent Scopus-indexed research on academic engagement. Records were retrieved from the Scopus database and limited to open-access, English-language journal articles in the psychology subject area published between 2021 and 2024. Of 40 records identified, 13 studies met all eligibility criteria. Four questions guided the synthesis, concerning the temporal distribution, research designs, populations, and geographic spread of the evidence. The results show that publication activity peaked in 2023 (five studies), that quantitative survey designs dominate the field (six studies), followed by mixed-methods (three), qualitative (two), and intervention-based designs (two). Contrary to common assumptions, twelve of the thirteen studies were conducted in higher education settings, and the corpus spans ten countries across five continents, with South Africa, Portugal, and China contributing two studies each. Six studies appeared in Q1 journals and six in Q2 journals, and the corpus has accumulated 184 citations, indicating the growing scholarly impact of the topic. The review concludes that pandemic-era disruption has repositioned academic engagement as a central lens for understanding technology-mediated learning, and it identifies longitudinal, qualitative, and Global South research as priority gaps for the next research cycle.